Makna Hidayah dan Dhalal Dalam Novel Tuhan Maha Asyik: Kajian Hermeneutik Berbasis Teologi Islam - Robi Nurhadi (Pascasarjana IAIN Metro, 2026)
This study analyzes the concepts of guidance (hidayah) and misguidance (dhalal) in Islamic perspective through a hermeneutical approach to two chapters, “Tersesat” (“Lost”) and “Pertanda” (“Sign”), from the novel Tuhan Maha Asyik. It combines a synthetic reading of Islamic exegesis based on the Qur’an and the concepts of ayat qauliyyah and ayat kauniyyah with interpretive reflection on key quotations from Sujiwo Tejo and M.N Kamba. This qualitative library research, employing textual hermeneutics and the hermeneutic circle, finds that “being lost” can be understood as a phase of spiritual searching that unfolds under God’s indirect guidance or as a divine indulgence, while “signs” refer to divine indications in everyday life that function as subtle pointers. The religious and sociological significance of a deeper understanding of hidayah and dhalāl lies in encouraging a more humble religiosity, avoiding hasty accusations of deviance, and cultivating sensitivity to God’s signs within lived experience. These findings are relevant to contemporary Islamic discourse, as they link a narrative of popular philosophy with Islamic theological values in an ethically responsible manner.